Protease and Phytohormone Production by Potassium solubilizers Isolated from Maize Rhizosphere - Nwokeh, Uchenna Jonathan; Soretire, Adeniyi Adebowale; Babalola, Oluwatoyin Abimbola; Akintokun, Aderonke Kofoworola (Direct Research Journal of Agriculture and Food Science, 2024)
Enzymes and phytohormones are essential substances required for plant development, especially at their vegetative stage. Microbial-plant-root interactions on rhizosphere region make possible for both nutrient mineralization and absorption. An in-vitro assessment was carried out to assess the protease, indole acetic and gibberellic acids production patterns by Lysinibacillus fusiformis and Providencia rettgeri.  Both bacterial strains produced indole acetic and gibberellic acids; two essential phytohormones necessary for seed germination and fruit ripening.  Time of incubation of both bacterial inoculants had significant effects (p
Keywords: Gibberellic acid; incubation time; indole acetic acid; protease; rhizobacteria